2018
DOI: 10.1002/msc.1236
|View full text |Cite
|
Sign up to set email alerts
|

Current physiotherapy practice in the management of tennis elbow: A service evaluation

Abstract: Wide variations in treatment approaches were identified. There was no consistency in the choice of modality used, the type of exercise or the dose of exercise prescribed. The use of passive modalities and corticosteroid injections was found to remain commonplace, despite a lack of supporting research evidence. There is a clear need for evidence-based guidance for physiotherapists treating patients with tennis elbow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…Some have suggested that a considerable amount of management in sports medicine is not supported by evidence. (26) It is noteworthy that health practitioners have a di cult time deciding between the research-based evidence, patient choice and their own clinical views (25,(27)(28)(29)(30)(31)(32)(33) so it should not be surprising that sports chiropractors are also a icted by this challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested that a considerable amount of management in sports medicine is not supported by evidence. (26) It is noteworthy that health practitioners have a di cult time deciding between the research-based evidence, patient choice and their own clinical views (25,(27)(28)(29)(30)(31)(32)(33) so it should not be surprising that sports chiropractors are also a icted by this challenge.…”
Section: Discussionmentioning
confidence: 99%
“…On day 16, the patient was instructed to begin adding eccentric and isotonic wrist extension and flexion exercises with the goals of building muscle endurance and encouraging proper remodeling of the tendon. The patient was able to complete moderate sets (2-4) and high repetitions (10)(11)(12)(13)(14)(15) at this time. These various types of contractions and exercises were continued for two weeks as weights and frequency progressed slowly.…”
Section: Rehabilitation Protocolmentioning
confidence: 91%
“…[13] In addition to the large variability in treatment options for refractory tennis elbow, there also exists a wide variation in rehabilitation treatment approaches with no certain consistency. [14] Additionally there is no consensus with respect to treatment after regenerative or orthobiologic procedures. [15] Finally, there are no established rehabilitation guidelines at all with respect to rehabilitation after a patient undergoes the Tenex procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Counterforce braces prevent extensor muscle expansion, creating a new extensor origin and giving the soft tissue time to heal. 8,50 It is possible that the better effect of the counterforce brace on pain in younger adults be the result of better remodeling capability of their musculoskeletal system in comparison to older adults. However, the effect of potential confounding variables like chronicity, the extent of intrasubstance damage, the severity of pain, and the extent of pressure on the tendon from the counterforce cuff should not be underestimated.…”
Section: Effects On Painmentioning
confidence: 99%
“…5,6 Although LET is commonly self-limiting and a waitand-see policy is frequently adopted, 7 many treatment strategies, including physiotherapy exercises, acupuncture, extracorporeal shock-wave therapy (ECSW), laser therapy, dry needling, orthoses, injections, and surgery, have been used to relieve pain, alleviate inflammation, and improve grip strength. 6,8,9 Conservative treatments result in clinical improvements in 75%-90% of subjects with LET. 10 A counterforce brace, which is also known as a "proximal forearm band" or "epicondylitis bandage," is one conventional treatment.…”
Section: Introductionmentioning
confidence: 99%